HUBUNGAN KEHARMONISAN KELUARGA DENGAN HASIL BELAJAR MATA PELAJARAN PRAKARYA SISWA SEKOLAH MENENGAH PERTAMA PATEAN - Partiyem Partiyem (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2016)
This study aimed to describe the harmony of family, the score of handicraf subject,and the corelation between the family harmony with the student score on the handicrafsubject of student class VII at SMP N 1 Patean Kendal Central Java in the year of 2014-2015. This study was a sample research.Data collecting methods used questionairesand documentation. Data analyzing methodsused descriptive and correlative analysis,hypothesis tested by using Product Momentthat was started by normality and linieritytest. This study shows that the harmony offamily level was in enough category49,66%the score of handicraf subject 64,83%. Basedon the result of Product Moment, the score ofr hitung > r tabel or 0,874 > 0,163, the result oft-tes t hitung > t tabel or 44,262 > 1,977, it canbe stated that there was a positive and significant correlation between the harmony of family with the score of handicraf subject ofstudent class VIISMP N 1 Patean KendalCentral Java in the year of 2014-2015